The Analysis of the Anticoagulant's Influence and Its Concentration on Clay Shale Dispersion in Hydrometer Testing - Pardoyo, Bambang; Wardani, Sri Prabandiyani Retno; Sari, Undayani Cita; Widodo, Tanur; Rafiando, Rafiando (Universitas Negeri Semarang, 2023)
Clay shale is a material that has the characteristic of being easily weathered if it is continuously exposed to the air. Based on this reason, further testing is needed for clay shale material to analyze the material characteristics, one of which is using a hydrometer test. In the hydrometer test, an anticoagulant breaks down the particles. Still, when the test was carried out by various laboratories with different types of samples, it would produce varying test results. This study aims to determine the effect of anticoagulant substances and their concentration on clay shale dispersion in the hydrometer test. The material used was clay shale from the Meteseh, Tembalang District, Semarang. This research method used was a hydrometer test based on British Standard 1377 Part 2 1990 and ASTM D7928-17 using seven anticoagulant agents. The results of the study using the British Standard 1377 Part 2 method showed that sodium polyphosphate, sodium pyrophosphate, and sodium hexametaphosphate were most influential in dispersing clay shale particles, which were characterized by a higher passing percentage of 0.042 mm and 0.002 mm when compared to other anticoagulants. Meanwhile, Calgon, sodium carbonate, sodium tripolyphosphate, and sodium silicate did not significantly affect the clay shale dispersion, indicated by the percentage that passed the sieve, which was not very high. Based on the British Standard 1377 Part 2 1990 and ASTM D7928-17 methods, the most optimum concentration in dispersing clay shale for sodium polyphosphate and sodium pyrophosphate is 5%, while for sodium hexametaphosphate is 6%.